The Role of SIBLING Proteins in Dental, Periodontal, and Craniofacial Development - Figueredo, Carlos Alberto; Abdelhay, Nancy; Gibson, Monica P. (Frontiers in Dental Medicine, 2022)
The majority of dental, periodontal, and craniofacial tissues are derived from the neural crest cells and ectoderm. Neural crest stem cells are pluripotent, capable of differentiating into a variety of cells. These cells can include osteoblasts, odontoblasts, cementoblasts, chondroblasts, and fibroblasts, which are responsible for forming some of the tissues of the oral and craniofacial complex. The hard tissue forming cells deposit a matrix composed of collagen and non-collagenous proteins (NCPs) that later undergoes mineralization. The NCPs play a role in the mineralization of collagen. One such category of NCPs is the small integrin-binding ligand, the N-linked glycoprotein (SIBLING) family of proteins. This family is composed of dentin sialophosphosprotein (DSPP), osteopontin (OPN), dentin matrix protein 1 (DMP1), bone sialoprotein (BSP), and matrix extracellular phosphoglycoprotein (MEPE). The SIBLING family is known to have regulatory effects in the mineralization process of collagen fibers and the maturation of hydroxyapatite crystals. It is well established that SIBLING proteins have critical roles in tooth development. Recent literature has described the expression and role of SIBLING proteins in other areas of the oral and craniofacial complex as well. The objective of the present literature review is to summarize and discuss the different roles the SIBLING proteins play in the development of dental, periodontal, and craniofacial tissues.